Economic Evaluation Economic Evaluation of Andesit Processing Plant at PT. Calvary Abadi in Somopuro Village Jogonalan Klaten - Mycelia Paradise,; Ag. Isjudarto,; H. Kresno, (ReTII, 2019)
ABSTRACT Calvary Abadi Klaten is an andesite processing plant located in Somopuro, Jogonalan, Klaten, Central Java. The average monthly total production is 51.000 m3. There are four products: 5mm-10mm split stone, 10mm-20mm split stone, 20mm-30mm split stone, and stone ash. The criteria used in this study are NPV (Net Present Value), IRR (Internal Rate of Return), and PBP (payback period). A project is feasible if it fullfills three conditions: NPV is bigger than zero, IRR is bigger than minimum interest rate specified (i *), and PBP is shorter than project life. Sensitivity analysis is used to determine the sensitivity of the project if some of its main variables changed. This study used two capital structures. The first capital structure was 60% own capital and 40% loan capital, and the second was 100% own capital. Based on the calculation results, the first capital structure obtained NPV = Rp. 12,857,234,525, IRR = 42.8%, and PBP = 2.97 years. And the second capital structure obtained NPV = Rp. 9,897,703,535, IRR = 30.1%, and PBP = 3.83 years. Based on the results above, can be concluded that andesite stone processing project at PT. Calvary Abadi Klaten is a feasible project. Based on sensitivity analysis, the project was still feasible when operating cost increased up to 10% and revenue (selling price) decreased up to 10%. Keyword : NPV, PBP, and Sensitivity analysis